Weak Systems. Unveiling the Vulnerabilities of Digitization - Bory, Paolo; Di Salvo, Philip (Tecnoscienza – Italian Journal of Science & Technology Studies, 2021)
This article discusses digitization weaknesses, biases, and malfunctions to challenge popular, almost hegemonic visions of contemporary technologies. By focusing on examples provided by recent mediated cases, controversies, and critical research about biases, we aim to propose an analysis of anything digital starting from its vulnerabilities, to look beyond polarized deterministic views, both optimistic and pessimistic. The article generates from the thematic track: “Weak Systems. Exploring bias, bugs and the vulnerability of digitization” that took place at the VIII STS Italia Conference. The panel brought together scholars from different backgrounds, including STS, history of technology, sociology of communication and critical data and media studies to discuss instances of technological weaknesses in various contexts. The article sums up some of the panel takeaways and pleas for a cooperative and interdisciplinary effort focusing on “weak systems”.